Features of using technology of project training to increase the interest of students studying biology - Байташева, Гауһар; Мусина, Айтжамал; Исаева, Ақмарал; Мырзабаева, Жанар; Сартаева, Ақмарал (Pedagogy and Psychology, 2020)
On the basis of the updated educational program were discussed issues of application of design technologies, in biology lessons in the section «Cell Biology» on the method of spiral training. Communication between parents, teachers and students is provided for in project technology. The point is that interest in the topic will increase by asking questions to parents. I was asked to voice my question, share my ideas through group work. The analysis of the works of these scientists is carried out and some stages of application are noted. In order to increase the interest of students studying the subject of biology, the specifics of the use of technology in project training are determined. In the field of biology are defined stages of work aimed at further development and consolidation of data on the topic «Cell Biology». The role of the teacher was shown. Highlighted the relationship of parents with children and friendship, communication in the classroom.